Effects of Ouabain in Ehrlich Tumor Development in vitro and in vivo - Amanda Costa Ayres Salmeron; Maria Beatriz Calado; Mateus da Silva Matias Antunes; Gabriel Rodrigues Da Silva; Deyse Cristina Madruga Carvalho; Beatriz Fernandes de Souza; Regina Piuvezam; Sandra Rodrigues-Mascarenhas (Biology, Medicine, & Natural Product Chemistry, 2023)
Ouabain (OUA) is a cardiotonic steroid with an immunomodulatory and anti-inflammatory role in different experimental models. Currently, the potential antineoplastic effect of OUA has been studied, however, research is needed to better understand OUA role during tumor development. Therefore, our aim was to investigate the OUA effects on Ehrlich tumor (ET) development in vitro and in vivo. To evaluate the cytotoxic effects of OUA on ET in vitro the cells were incubated with different concentrations of OUA during 24h and 48h and our results showed that only the [1000 ?M] decreased the number and viability of ET cells in the two analyzed times. To study the OUA effects on ET in vivo, Swiss mice were pretreated with 0.56 mg/kg of OUA intraperitoneally (i.p.) for three consecutive days. To develop ET in the solid form, one hour after the last day of pretreatment, ET cells were inoculated subcutaneously into the footpad and the animals were monitored for 13 days. To develop the ascitic form, ET cells were inoculated (i.p.) and the animals were monitored for 3 days. OUA was able to reduce the thickness and weight of the tumor paw, in addition to reduce the weight of the popliteal lymph node. In the ascitic tumor, OUA reduced the number of neutrophils and macrophages and increased the lymphocytes in the peritoneum. Thus, we demonstrated that OUA affects ET development both in vitro and in vivo. Our results suggest a new perspective in the anti-inflammatory, immunomodulatory and a possible anti-cancer role of ouabain and brings new concepts about the pathophysiological role of this substance.